Bio-photoelectrochemical degradation, and photocatalysis process by the fabrication of copper oxide/zinc cadmium sulfide heterojunction nanocomposites: Mechanism, microbial community and antifungal analysis. (December 2022) - Lei, Chao; Sun, Nabo; Wu, Huizhen; Zhao, Yonggang; Yu, Cun; Janani, Baadal Jushi; Fakhri, Ali
Abstract: In this work, the fabrication of the CuO on ZnCdS as a heterojunction nanocomposites were conducted by hydrothermal method and the synthesis method was confirmed by the XRD, XPS, EDS, UV–vis spectrum analysis. The CuO/ZnCdS was used as a photocathode in the bio-photoelectrochemical system (BPES) for tetracycline (TC) degradation under solar irradiation. The CuO/ZnCdS photocathode indicated substantial photocatalytic efficiency for TC degradation, due to the fast separation and transfer of photogenerated carriers. The ESR test evaluates the mechanism of degradation, and shows that ·OH, and ·O2 − were contributed to TC degradation. The TC degradation was 1.59 times higher than the unilluminated process (98.72% vs 61.71). The photocatalysis test shows that the TC was degraded about 90.5% in 1.5 h. Then, the synthesized CuO/ZnCdS nanocomposites were studied for the biological application such as antifungal activities. CuO/ZnCdS nanocomposites depicted substantial antimicrobial activity versus Candida-albicans by in vitro process. Therefore, this study suggests the novel system for the antibiotics degradation, and as antifungal application. Graphical abstract: Image 1 Highlights: Efficient CuO/ZnCdS photocathode was developed for BPESs. The O2 −, OH and ·CO3 − promoted TC removal in BPESs with NaHCO3 . Pseudomonas and Acinetobacter capable to degrade TC were detected on bioanode. Possible TC degradation mechanism and pathways in the BPES were proposed. CuO/ZnCdS nanocomposites depicted substantial activity versus Candida-albicans.